(untitled) (Research, Society and Development, 2021)
This work aims to discuss the concept of experience brought by Larrosa (2002), in the text Notes on experience and knowledge of experience, in the teacher’s formative process, from the perspective of pedagogical documentation along with other authors. From this, we present narratives that deal with concepts such as: Early Childhood Education, pedagogical documentation, teacher training, experience and its interfaces based on several bibliographic studies. Finally, we highlight the role of pedagogical documentation, as a learning experience for teachers, enabling their constant teacher training.